Financing child rights in Malawi - Rachel Etter-Phoya; Chisomo Manthalu; Frank Kalizinje; Farai Chigaru; Bernadetta Mazimbe; Ajib Phiri; Takondwa Chimowa; Waziona Ligomeka; Stephen Hall; Bernadette O'Hare (BMC, 2023)
Abstract Background Nearly all countries have ratified the United Nations Convention on the Rights of the Child and, therefore, support children having access to their rights. However, only a small minority of children worldwide have access to their environmental, economic, and social rights. The most recent global effort to address these deficits came in 2015, when the United Nations General Assembly agreed to a plan for a fairer and more sustainable future by 2030 and outlined the Sustainable Development Goals (SDGs). One remediable cause is the lack of revenue in many countries, which affects all SDGs. However, illicit financial flows from low-income to high-income countries, including international tax abuse, continue unabated. Methods Using the most recent estimates of tax abuse perpetuated by multinational companies and tax evasion through offshore wealth, and precise econometric modelling, we illustrate the potential regarding child rights (or progress towards the SDGs) if there was an increase in revenue equivalent to tax abuse in Malawi, a low-income country particularly vulnerable to climate change. The Government Revenue and Development Estimations model provides realistic estimates of government revenue changes in developmental outcomes. Using panel data on government revenue per capita, it models the impact of increased revenue on governance and SDG progress. Results If cross-border tax abuse and tax evasion were curtailed, the equivalent increase in government revenue in one country, Malawi, would be associated with 12,000 and 20,000 people having access to basic water and sanitation respectively each year. Each year, an additional 5000 children would attend school, 150 additional children would survive, and 10 mothers would survive childbirth. Conclusions More children would access their economic and social rights if actions were taken to close the gap in global governance regarding taxation. We discuss the responsibility of duty bearers, the need for a global body to arbitrate and monitor international tax matters, and how the Government of Malawi could take further domestic action to mitigate the gaps in global governance and protect itself against illicit financial flows, including tax abuse.